Adriano Spatola, Malebolge e la proposta di un Parasurrealismo - La Rosa, Emanuele (Verbum – Analecta Neolatina, 2013)
The paper discusses Adriano Spatola’s proposal of a “Parasurrealism” through a short review of Malebolge. Together with other writers (especially Giorgio Celli), Spatola suggested that a retake of the processes of French Surrealism was a possible way to rejuvenate Italian neo-avantgarde poetry. Here we analyze the theoretical interventions of the authors, plus one of Spatola’s poetic texts, with the intent to explain the purpose of this operation.